Artificial intelligence in education promises and implications for teaching and learning - Holmes, Wayne; Bialik, Maya; Fadel, Charles (Center for Curriculum Redesign, 2019)
"A must read for educators and all stakeholders interested in how the future of education will be impacted - and more than likely transformed - by AI ... provides a critical leans on both the potential benefits and risks of AI without hyping the technology."--
Keywords: Künstliche Intelligenz; Bildungswesen; Artificial intelligence / Educational applications; Computer-assisted instruction; Intelligent tutoring systems; Intelligence artificielle / Applications en éducation; Enseignement assisté par ordinateur; Tutoriels